2023
DOI: 10.3390/app13137840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flax Cake and Lupine Flour Addition on the Physicochemical, Sensory Properties, and Composition of Wheat Bread

Abstract: Bread is consumed by people all over the world. Its quality may be modified by the application of other raw materials or changes in production technology. The addition of flax cake (FC) and lupine flour (LF) was proposed as a modification of the nutritional value of wheat bread. Bread with non-fermented and fermented FC and LF was prepared, and its physicochemical, sensory properties and composition were compared to wheat bread. A higher than 5% addition of these components reduced the bread volume and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…One of the key factors determining bread quality is the loaf volume. Loaves with a larger volume are generally more appealing to consumers [6]. SV ranged from 2.82 cm 3 •g −1 to 2.29 cm 3 •g −1 , with the maximum value observed in the control sample, and it decreased with the incorporation of vegetable by-products.…”
Section: Evaluation Of Bread Quality Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…One of the key factors determining bread quality is the loaf volume. Loaves with a larger volume are generally more appealing to consumers [6]. SV ranged from 2.82 cm 3 •g −1 to 2.29 cm 3 •g −1 , with the maximum value observed in the control sample, and it decreased with the incorporation of vegetable by-products.…”
Section: Evaluation Of Bread Quality Characteristicsmentioning
confidence: 95%
“…Regarding total global food production, the amount of food wasted is estimated to be around 1.3 billion tons. Utilizing by-products from food processing that are rich in nutrients in new product development is a recommended approach for alleviating this [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Wirkijowska et al [17], Guo et al [126], Makowska et al [145], Krupa-Kozak et al [146], and Gao et al [147] focused on assessing the impact of adding flaxseed cake, flour, and waste flaxseed extract on the sensory characteristics of bread. In the study by Wirkijowska et al [17], it was observed that a 10% addition of flaxseed pomace results in bread with acceptable sensory properties.…”
Section: Sensory Quality and Consumer Acceptancementioning
confidence: 99%
“…Similarly, Guo et al [126] reported a decrease in color assessment during sensory evaluation with additions of flaxseed cake, suggesting that the darker color of the bread was less attractive to the assessors. Makowska et al [145] conducted a study on wheat bread using a sensory panel in accordance with ISO 8586-1:1993 [146]. The study involved evaluating the color, taste, aroma, texture, and overall acceptability of bread samples by ten judges.…”
Section: Sensory Quality and Consumer Acceptancementioning
confidence: 99%